Weight of Pregnant Women in Deli Serdang Regency: A Qualitative Study - Nur Mala Sari; Nur Indrawaty Lipoeto; Adang Bachtiar; Ariadi Ariadi; Rizanda Machmud; Defrin Defrin; Mudjiran Mudjiran; Delmi Sulastri (Indonesian Journal of Global Health Research, 2024)
Weight gain that is not according to recommendations during pregnancy has become an epidemic throughout the world today and is a clinical problem with high prevalence and can affect the health of mothers and babies. Objective: This study aims to find out more about the perspective of increase in weight of pregnant women in deli serdang regency. Method: This study was qualitative with a descriptive approach. The informants in this study were 3 pregnant women with weight gain above recommendations, 3 pregnant women with weight gain below recommendations, 1 ob-gyn, 1 midwife, and 1 nutrition who were recruited using purposive sampling. Data were collected using semi-structured interviews. Data were analyzed using the Content Analysis. Results: The study emerged 5 themes: (1) Knowledge, (2) Perspective, (3) Behaviour, (4) Family support, and (5) Physical activity. Conclusions: The findings show that several factors influence the increase in weight of pregnant women in Deli Serdang Regency, so the health care provider needs to pay attention to improve their knowledge about weight gain during pregnancy according to the needs of pregnant women.